2013
DOI: 10.1242/jeb.082248
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of expression of metabolic genes and microRNAs in rainbow trout alevins during the transition from the endogenous to the exogenous feeding period

Abstract: SUMMARYAs oviparous fish, rainbow trout change their nutritional strategy during ontogenesis. This change is divided into the exclusive utilization of yolk-sac reserves (endogenous feeding), the concurrent utilization of yolk reserves and exogenous feeds (mixed feeding) and the complete dependence on external feeds (exogenous feeding). The change in food source is accompanied by well-characterized morphological changes, including the development of adipose tissue as an energy storage site, and continuous muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 85 publications
2
37
2
1
Order By: Relevance
“…Thus, taking into consideration all duplicated genes encoding gluconeogenic enzymes, our results suggested maintenance of an active gluconeogenic pathway during nutritional transition and no inhibition in alevins utilizing an exogenous diet, as previously proposed by Mennigen et al (2013). There was a decrease in the mRNA levels of two genes involved in the last step of glucose release at the first meal, i.e.…”
Section: Studying Duplicated Glucose Metabolism-related Genes New Inssupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, taking into consideration all duplicated genes encoding gluconeogenic enzymes, our results suggested maintenance of an active gluconeogenic pathway during nutritional transition and no inhibition in alevins utilizing an exogenous diet, as previously proposed by Mennigen et al (2013). There was a decrease in the mRNA levels of two genes involved in the last step of glucose release at the first meal, i.e.…”
Section: Studying Duplicated Glucose Metabolism-related Genes New Inssupporting
confidence: 85%
“…The conservation of an active gluconeogenic pathway in exogenous feeding alevins as well as in juveniles (Marandel et al, 2015;Seiliez et al, 2011) fed without dietary carbohydrates thus made it possible to sustain endogenous glucose demands for the maintenance of normoglycaemia (Cowey et al, 1981;French et al, 1981;Cowey, 1979, 1983). Moreover, genes involved in the glycolytic pathway were maintained ( pfkl paralogues and pklr gene) or only weakly increased expression (gck genes) with advancing nutritional transition, confirming the observations of Mennigen et al (2013).…”
Section: Studying Duplicated Glucose Metabolism-related Genes New Inssupporting
confidence: 73%
See 1 more Smart Citation
“…We previously found that the transition from endogenous to exogenous feeding altered the expression of the studied miRNAs in trout alevins [(Mennigen et al, 2013) except for miRNA-107]. However, the drastic change in macro-nutrient intake at first feeding did not modify their expression level in the present study.…”
Section: Research Articlecontrasting
confidence: 65%
“…The trout alevins were fed from first-feeding (at mouth opening) diets with low or high carbohydrate/protein ratio and then challenged to eat a high-carbohydrate diet at the later juvenile stage. Compared with mammals, trout alevins (larvae) constitute a powerful and unique model with which to try to modify metabolism because of the very high plasticity (Pittman et al, 2013, Mennigen et al, 2013 and the direct acceptability of exogenous solid feed at this developmental stage. Indeed, drastic changes in metabolic gene expression occur in first-feeding rainbow trout, during the transition from endogenous (yolk-sac) to exogenous feeding, as illustrated for some genes involved in carbohydrate utilisation (Geurden et al, 2007) and for the expression of miRNAs that may contribute to the ontogenetic metabolic changes (Mennigen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%